A new species of the Pleistocene furnariid Pseudoseisuropsis (Aves, Passeriformes) - Stefanini, Manuel Ignacio (2016)
Pseudoseisuropsis wintu sp. nov. is described from cranial material that had formerly been designated as a paratype of the extinct Pseudoseisuropsis nehuen. Thorough comparisons were made between the cranial specimens ascribed to Pseudoseisuropsis and many extant furnariid species. This new species is lower Pleistocene in age and increases the known diversity of Pseudoseisuropsis to three species. Cladistic analyses were performed using 43 cranial characters and a backbone constraint based on a well-supported phylogeny from a recent molecular analysis. In the most parsimonious tree, Pseudoseisuropsis was retrieved as a sister group of woodcreepers (Dendrocolaptinae) with low support. However, slightly suboptimal hypotheses, which could not be completely ruled out, suggest that this genus may be more closely related to other clades of Furnariidae. Hence, we agree with previous authors in regarding Pseudoseisuropsis as Furnariidae Incertae sedis. In addition, two fragmentary fossils ascribed to Pseudoseisuropsis were included in taxonomic comparisons: P. cuelloi, in order to assess the possibility that P. wintu sp.nov. belongs to that species, and another paratype of P. nehuen, to reassess its taxonomic identity.